Anti-inflammatory activities of Ganoderma lucidum (Lingzhi) and San-Miao-San supplements in MRL/lpr mice for the treatment of systemic lupus erythematosus. Issue 1 (December 2016) - Cai, Zhe; Wong, Chun; Dong, Jie; Jiao, Delong; Chu, Man; Leung, Ping; Lau, Clara; Lau, Ching; Tam, Lai; Lam, Christopher
Abstract Background Ganoderma lucidum (Lingzhi ; LZ) andSan -Miao -San (SMS) are Chinese medicines (CMs) used to treat inflammatory ailments and numbing syndrome/arthralgia syndrome (Bi Zheng ), respectively. Given that the main symptoms of systemic lupus erythematosus (SLE) include inflammation of the joints, joint pain, edema and palpitations of the heart because of problems associated withBi Zheng, it was envisaged that LZ and SMS could be used as potential treatments for this autoimmune disease. This study aims to investigate the anti-inflammatory activity of a combination formulation containing LZ and SMS (LZ–SMS) in SLE mice. Methods Female adult Balb/c mice of 20–24 weeks of age were used as normal mice (n = 10), whereas female MRL/lpr mice of 12–24 weeks of age were divided into three groups (n = 10 in each group), including mild, moderate and severe SLE mice groups. The clinical characteristics of the SLE and Babl/c mice (i.e., body weight, joint thickness, lupus flare, proteinuria, leukocyturia and lymphadenopathy) were assessed. The plasma concentrations of anti-nuclear antibody (ANA) and anti-double stranded DNA antibody (anti-ds-DNA) were analyzed by an enzyme-linked immunosorbent assay, whereas the concentration of several key cytokines (IFN-γ, TNF-α, IL-6, IL-10, IL-2, IL-27, IL-12P70, IL-17A and IL-21) were analyzed by a Luminex multiplex assay. The gene expression profiles for differentiation of the T helper (Th) lymphocytes in splenic CD4+ Th cells were assessed by RT-qPCR. Flow cytometry was used to measure the percentages of CD4+ CD25+ Foxp3+ Treg cells and CD19+ CD5+ CD1d+ IL-10+ regulatory B (Breg) cells (IL-10+ Bregs). Results Concentrations of anti-ds-DNA in the plasma samples collected from the LZ–SMS-treated (500 mg/kg/day oral administration for 7 days followed with 50 mg/kg/day intraperitoneal administration for 7 days), moderate and severe SLE mice decreased significantly compared with the PBS treated mice (P < 0.05). The gene expression levels of the induced regulatory T (iTreg) and natural Treg (nTreg) cells were significantly higher than those of the Th17, Th1 and "conventional Th cells vs. Treg cells" regulated genes following the LZ–SMS treatment (P < 0.05). The percentages of CD4+ CD25+ Foxp3+ Treg cells collected from the splenic, thymic and peripheral blood cells, as well as the percentages of IL-10+ Bregs collected from the splenic and thymic cells increased significantly in the LZ–SMS-treated SLE mice (P < 0.05) compared with the untreated PBS group. The ratio of the percentage of CD4+ CD25+ Foxp3+ Treg cells to the percentage of CD4+ CD25– effector T cells collected from the splenic, thymic and peripheral blood cells in LZ–SMS-treated moderate and severe SLE mice increased significantly compared with the untreated PBS group (P < 0.05). Furthermore, a comparison with the PBS treatment group revealed significant decreases in the concentrations of several inflammatory cytokines, including IL-21, IL-10 and IL-17A (P < 0.05), as well as significant increases in the concentrations of IL-2 and IL-12P70 in the LZ–SMS treated SLE mice (P < 0.05). Conclusion LZ–SMS treatment led to significant increases in the percentages of CD4+ CD25+ Foxp3+ Treg and IL-10+ Breg cells, together with a reduction in the plasma concentrations of several inflammatory cytokines and the down-regulated expression of the corresponding cytokine related genes in SLE mice. The clinical characteristics of the LZ–SMS-treated SLE mice also improved significantly.